Fiscal Policy, Public Spending and the 2015 General Election - Nicholas Sowels (Revue Française de Civilisation Britannique)
The general elections in May 2015 took place against a fair, but mixed economic background. After three years in the previous parliament when the UK economy had been flat-lining (mid-2010 to mid-2013), partly as a result of the Coalition’s policy of fiscal consolidation, the pick-up in activity during the second half of 2013 provided the outgoing government with a reasonable economic record to present to the electorate. The three main parties – the Conservatives, the Liberal Democrats and Labour – all ran manifestos based on fiscal responsibility, as in some ways did UKIP. Only the SNP proposed a clearer leftwing agenda based on stronger public services and higher taxation. Given the outcome of the elections, the Conservatives appear to have had a more successful electoral strategy, in which they succeeded in portraying themselves as economically competent while characterising Labour as having wrecked the economy during the Blair-Brown years. Yet the economy was not the only major issue to have shaped the electoral results. Since resuming office unexpectedly, the Conservatives have pursued the policy of deficit and debt reduction begun under the Coalition, as part of a tougher neo-Thatcherite approach.